Pengembangan Pembelajaran Berbasis Blended Learning Pada Mata Pelajaran Etimologi Multimedia - Banggur, Maria Dissriany Vista; Situmorang, Robinson; Rusmono, Rusmono (JTP - Jurnal Teknologi Pendidikan, 2018)
: The purpose of this study was to develop blended learning-based learning on multimedia etymology subjects. This research develops face-to-face learning combined with online / offline learning and arranged using Edmodo platform. The method used is research and development, with a system approach referring to the Dick Carey and Carey model. The stage of product trials begins with material experts, media experts and learning design experts. Then the product was tested for XMM class students, namely one to one trials, small groups and large groups. The average score of the expert media was 3.52 or good, 4.00 material or very good and 3.73 learning design expert was good. In the testing phase for students the average score for one to one is 3.09, in the small group is 3.01 and in the large group is 3.40. The conclusion of the study is that blended learning-based learning in subjects of multimedia etymology is good and worthy of use.